2021
DOI: 10.3390/molecules26195891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wine Components in Inflammatory Bowel Diseases

Abstract: With the rising prevalence of Inflammatory bowel disease (IBD) worldwide, and the rising cost of treatment with novel biological drugs, there is an increasing interest in various diets and natural foods as a potential way to control/modulate IBD. As recent data indicates that diet can modify the metabolic responses essential for the resolution of inflammation, and as wine compounds have been shown to provide substantial anti-inflammatory effect, in this review we aimed to discuss the current evidence concernin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 84 publications
(131 reference statements)
0
8
0
Order By: Relevance
“…While the oxysterol treatment increased the production of pro-inflammatory cytokines and ROS species, the addition of EVOO phenols significantly reduced cytokine secretion and inhibited ROS production and MAPK phosphorylation [40]. Interestingly, analogous findings were reported in studies exploring the effects of wine polyphenols in modulating gut inflammation [19]. Namely, a study by Guina et al demonstrated how wine polyphenols counteracted the aforementioned effect of oxysterols by inhibiting the NOX1/p38 MAPK/NFκB signalling axis [41].…”
Section: The Evidence In Vitromentioning
confidence: 52%
See 1 more Smart Citation
“…While the oxysterol treatment increased the production of pro-inflammatory cytokines and ROS species, the addition of EVOO phenols significantly reduced cytokine secretion and inhibited ROS production and MAPK phosphorylation [40]. Interestingly, analogous findings were reported in studies exploring the effects of wine polyphenols in modulating gut inflammation [19]. Namely, a study by Guina et al demonstrated how wine polyphenols counteracted the aforementioned effect of oxysterols by inhibiting the NOX1/p38 MAPK/NFκB signalling axis [41].…”
Section: The Evidence In Vitromentioning
confidence: 52%
“…In recent times, the MedDiet and its specific components are increasingly being researched and used to prevent and manage chronic non-communicable diseases [16][17][18]. In addition, there is compelling new evidence about the efficacy of various nutraceuticals, such as the polyphenols from natural foods like olive oil and wine, in modulating IBD [19,20]. Olive oil, and especially extra virgin olive oil (EVOO), with its high content of mono-unsaturated fatty acids (MUFAs), tocopherols, and polyphenols, is thought to be one of the main bioactive compounds found in the MedDiet [21].…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained in another meta-analysis that also studied the relationship between a posteriori dietary patterns and MetS: a healthy/prudent diet was associated with a lower prevalence of MetS, while an unhealthy/Western pattern was associated with an increased risk of developing MetS [ 64 ]. Another popular dietary pattern, the Mediterranean diet, has also shown benefits regarding MetS [ 65 , 66 ]. In a meta-analysis by Kastorini et al, the combined effect of prospective studies and clinical trials showed that the Mediterranean diet is associated with a reduced risk of MetS (log hazard ratio: −0.69, 95% confidence interval (CI): −1.24 to −1.16) [ 67 ].…”
Section: Effects Of Diet On Metabolic Syndromementioning
confidence: 99%
“…Thus, the inhibitory effects of red wine on inflammatory mechanisms, such as NF-kB activation, IL-8 production, COX-2 and inducible nitric oxide synthase induction, provide evidence that polyphenols are able to ameliorate or prevent intestinal inflammation [ 13 ]. Currently, there is already preclinical data that suggest a beneficial role of several specific bioactive compounds present on wine, mainly resveratrol, in several inflammatory-related disorders [ 20 , 21 ]. However, there is a lack of evidence concerning what the exact role of a more complete extract, including different phenolic compounds present on red wine, in an IBD context might be.…”
Section: Introductionmentioning
confidence: 99%